Overconsumption, Procreation, and Morality - Mariana, John (ETHICS IN PROGRESS, 2014)
Thomas Young (2001) argues that overconsumption and procreation are morally equivalent, and thus that anyone who disapproves of overconsumption must arrive at the same normative judgment concerning procreation (or procreation beyond a certain threshold). Young presents an analogical argument in support of his claim, and defends it against four varieties of objections intended to show that the analogy is weak or faulty. I argue that Young’s defense of his argument fails, and that though a stronger case can be made for his claim of moral equivalence between procreation and overconsumption, a full defense of the claim would unfortunately require a moral theory that we presently do not have (namely, Derek Parfit’s Theory X, the theory of beneficence that would tell us how many people there should be). This is unfortunate because in the absence of successful rational grounds for such a claim concerning the moral value (or disvalue) of procreation relative to resource consumption, we are likely to overlook or misjudge the moral and other costs of population growth.